CITRA MANUSIA DALAM TEOLOGI KRISTEN: Sebuah Tinjauan Humanis Terhadap Imago Dei - Ocsilia Imel Patibang; Yunirma, Yoan Putri Kalista, Cristina Midian, Mutiara (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
The concept of Imago Dei (the image of God) is one of the central pillars of Christian theology, defining human identity and dignity. This study aims to explore the theological understanding of Imago Dei through a literature-based approach and examine its relevance in fostering humanistic values such as equality, justice, freedom, empathy, and social responsibility. By analyzing various interpretive models of Imago Dei: substantial, relational, and functional. This paper demonstrates that the image of God in humanity not only carries a spiritual dimension but also serves as a normative foundation for the defense of universal human rights and dignity. In a world marked by humanitarian crises, discrimination, and dehumanization, this doctrine emerges as a bridge between Christian faith and public ethics, offering insights that are vital for shaping a more humane and compassionate society. This reflection also affirms that honoring humanity is a tangible expression of obedience to God as the Creator